Pengaruh Kompetensi Profesionalisme Dan Tekanan Waktu Terhadap Kualitas Audit Pada Kantor Akuntan Publik Di Kota Makassar - Hadriana Hanafie; Miftahul Fatihah; Baso R; Sumarni S (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Audit quality is an important indicator in maintaining the credibility of financial statements and public trust in the accounting profession. This study aims to analyze the effect of professional competence and time pressure on audit quality at Public Accounting Firms (KAP) in Makassar City. The study employed a quantitative approach using primary data collected through questionnaires distributed to auditors working in public accounting firms. The sample consisted of 30 auditors selected using probability sampling techniques. Data analysis was conducted using multiple linear regression with IBM SPSS version 26. The results indicate that professional competence has a positive and significant effect on audit quality with a regression coefficient of 0.813 and a significance value below 0.05. Time pressure shows a positive coefficient of 0.179 but does not significantly affect audit quality. Simultaneously, professional competence and time pressure significantly affect audit quality, as evidenced by an F-value of 13.196 and a significance level below 0.001. These findings imply that strengthening auditor competence through education, training, and professional experience is crucial to improving audit quality